Human TFIIH Kinase CDK7 Regulates Transcription-Associated Chromatin Modifications - Christopher C. Ebmeier (Cell Reports, 2017)
Summary: CDK7 phosphorylates the RNA polymerase II (pol II) C-terminal domain CTD and activates the P-TEFb-associated kinase CDK9, but its regulatory roles remain obscure. Here, using human CDK7 analog-sensitive (CDK7as) cells, we observed reduced capping enzyme recruitment, increased pol II promoter-proximal pausing, and defective termination at gene 3′ ends upon CDK7 inhibition. We also noted that CDK7 regulates chromatin modifications downstream of transcription start sites. H3K4me3 spreading was restricted at gene 5′ ends and H3K36me3 was displaced toward gene 3′ ends in CDK7as cells. Mass spectrometry identified factors that bound TFIIH-phosphorylated versus P-TEFb-phosphorylated CTD (versus unmodified); capping enzymes and H3K4 methyltransferase complexes, SETD1A/B, selectively bound phosphorylated CTD, and the H3K36 methyltransferase SETD2 specifically bound P-TEFb-phosphorylated CTD. Moreover, TFIIH-phosphorylated CTD stimulated SETD1A/B activity toward nucleosomes, revealing a mechanistic basis for CDK7 regulation of H3K4me3 spreading. Collectively, these results implicate a CDK7-dependent “CTD code” that regulates chromatin marks in addition to RNA processing and pol II pausing. : Ebmeier et al. use targeted proteomics to identify distinct interactomes for full-length mammalian pol II CTD phosphorylated by TFIIH or P-TEFb. In vitro and cell-based assays uncover expanded roles for the TFIIH-associated kinase CDK7, including regulation of SETD1A/B methyltransferase activity and regulation of transcription-associated histone modifications (i.e., H3K4me3 and H3K36me3). Keywords: RNA-seq, proteomics, Mediator, THZ1, chromatin, epigenetic, TFIIH, P-TEFb, H3K4me3, H3K36me3